(untitled) (Proceedings of International Conference on Special Education, 2015)
This paper determined disable student perceptions when using web application in learning. Students will have an opportunity to showcase their learning in Padlet and share it to social media. Padlet is a free web application which gives students the easiest way to create and collaborate in the world. This research will demonstrate whether by using Padlet is easy or difficult for disable student to operate the application and adapt it with their learning process. The Technology Acceptance Model (TAM) use to gather user reactions to examines users’ perceptions of Usage, Usefulness, and Ease of Use. This research applied the TAM to all special needs students with hearing impaired and learning disability in Selayang Community College. TAM will measure their reactions to Padlet. Findings indicate that most of the students shows their interest to use Padlet and believe by using Padlet would improve their job performance. They also agreed the application is clear and easy to understand. However, Padlet also requires lots of their mental effort. Padlet can be the tools to showcase disable students portfolio and communicate their abilities better to the world.